From the elastocaloric effect towards an efficient thermodynamic cycle. (1st October 2022) - Kabirifar, Parham; Trojer, Jonas; Brojan, Miha; Tušek, Jaka
Abstract: In recent years, elastocaloric cooling technology has been considered as one of the most promising alternatives to vapor compression technology. Given that elastocaloric technology is only in the early stages of development, a uniform method for evaluating the elastocaloric effect has not yet been established, and the thermodynamics of different elastocaloric cooling cycles have not yet been studied in detail. Therefore, the main goal of this work is to investigate these two important areas. Here, multiple thermodynamic cycles were studied, focusing on the parameters of the holding period of the cycle, which is essential for heat transfer between the elastocaloric material and the heat sink/source. The cycles were applied to commercially available superelastic thin-walled NiTi tubes under compressive loading and a thin NiTi wire under tensile loading. Isostress cycles with constant stress throughout the holding period, isostrain cycles with constant strain throughout the holding period and no-hold cycles (without a holding period) were studied across multiple stress/strain ranges. Based on the experimental results, a previously developed phenomenological model was applied to better understand and further evaluate the different cycles. The results revealed that the applied thermodynamic cycle significantly affects the thermomechanical response and thus the cooling/heating efficiency of the elastocaloric material. We show that by using isostress cycles and partial transformations, a Carnot-like thermodynamic cycle with improved heating/cooling efficiency can be generated. By applying the isostress cycles, an adiabatic temperature change of 30.2 K was measured, which is among the largest directly measured reproducible adiabatic temperature changes reported for any caloric material to date. Ultimately, this study intends to serve as a basis for establishing a uniform method for evaluating the elastocaloric effect in different materials that would allow for reliable and accurate one-to-one comparison of the reported results in the rapidly growing field of elastocalorics.